2021
DOI: 10.1111/1365-2745.13688
|View full text |Cite
|
Sign up to set email alerts
|

Worlds apart: Location above‐ or below‐ground determines plant litter decomposition in a semi‐arid Patagonian steppe

Abstract: 1. While considerable attention has been devoted to how precipitation modulates net primary productivity in arid and semi-arid ecosystems, the emergence of multi-faceted controls on carbon (C) turnover suggests that there is much to be understood with respect to the mechanistic controls on plant litter decomposition.2. In the Patagonian steppe, we conducted a long-term factorial experiment, evaluating the importance of position, litter quality, tissue origin and soil resources on rates of C turnover under natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 99 publications
0
27
0
Order By: Relevance
“…The role of photodegradation in litter decomposition is well established [ 84 , 112 ]. There is now more evidence that photodegradation plays a key role in moist and temperate systems, such as in temperate forests [ 117 ], as well as in dryland systems [ 118 , 119 ]. How much plant litter gets exposed to solar radiation, including the UV component, varies among ecosystems.…”
Section: Biogeochemical Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of photodegradation in litter decomposition is well established [ 84 , 112 ]. There is now more evidence that photodegradation plays a key role in moist and temperate systems, such as in temperate forests [ 117 ], as well as in dryland systems [ 118 , 119 ]. How much plant litter gets exposed to solar radiation, including the UV component, varies among ecosystems.…”
Section: Biogeochemical Cyclesmentioning
confidence: 99%
“…How much plant litter gets exposed to solar radiation, including the UV component, varies among ecosystems. In dryland ecosystems, litter is left on the ground in the dry season but burial can reduce exposure [ 119 ], while in temperate forests litter becomes exposed when gaps form in the canopy [ 117 ]. Fire also reduces vegetation cover and temporarily increases exposure to solar radiation [ 120 ].…”
Section: Biogeochemical Cyclesmentioning
confidence: 99%
“…For example, root mass was positively related to SOC accrual following 27 years of N addition at Cedar Creek in Minnesota, USA (CDR) (Fornara & Tilman, 2012), while lignin-rich root litter promoted soil C stabilization under N fertilization (Dijkstra et al, 2004). Meanwhile, in a dryland site, belowground inputs were the primary contributor to SOM, yet the high lignin content of roots appeared to constrain SOM formation (Berenstecher et al, 2021). In a companion study to this one (at the same NutNet sites), N and P stimulated aboveground biomass but productivity belowground was insensitive to N addition and increased less with P addition (Keller et al, 2017(Keller et al, -2018.…”
Section: Fertilization Effects On Soil C Poolsmentioning
confidence: 99%
“…Gallo et al ., 2009; Brandt et al ., 2010; Rutledge et al ., 2010; Baker & Allison, 2015; Gaxiola & Armesto, 2015; Austin et al ., 2016; Huang et al ., 2017; Huang & Li, 2017; Day et al ., 2018; Wu et al ., 2018; Marinho et al ., 2020; Keiser et al ., 2021), have shown that exposure to solar radiation can accelerate litter decomposition directly (through photochemical mineralization; Austin & Vivanco,2006; Brandt et al ., 2009; Lee et al ., 2012) and indirectly (through stimulation of biotic decomposition, that is, photofacilitation; Foereid et al ., 2010; Austin et al ., 2016). The magnitude of C loss deriving directly from volatile products of photodegradation is most evident in seasonally dry or arid ecosystems (Austin & Vivanco, 2006; Austin & Ballaré, 2010; Rutledge et al ., 2010; Ma et al ., 2017; Berenstecher et al ., 2020, 2021), but photofacilitation appears to be important in a broad range of ecosystems, with almost universal stimulation of biotic decomposition of plant litter that has been exposed to sunlight (e.g. Brandt et al ., 2010; Foereid et al ., 2010; King et al ., 2012; Araujo & Austin, 2015; Baker & Allison, 2015; Gaxiola & Armesto, 2015; Austin et al ., 2016; Gliksman et al ., 2018; Méndez et al ., 2019; Pieristè et al ., 2019; Day et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent conceptual framework for how leaf litter decomposes and returns C to the atmosphere as CO 2 suggests that there is not a strong hierarchy of global, regional and local controls on C turnover, with all controls demonstrating importance at different scales (Cornwell et al ., 2008; Pietsch et al ., 2014; Keiluweit et al ., 2015; Bradford et al ., 2016; Bradford et al ., 2017). As such, an updated vision of the controls on leaf and root litter decomposition is emerging (Hättenschwiler & Jørgensen, 2010; Cotrufo et al ., 2013; Bradford et al ., 2017; See et al ., 2019; Berenstecher et al ., 2020, 2021), coupled with the identification of underappreciated controls on plant litter decomposition such as sunlight exposure (Austin & Vivanco, 2006; Brandt et al ., 2009; Lee et al ., 2012), litter position (Liu et al ., 2015; Gliksman et al ., 2018; Berenstecher et al ., 2021) and precipitation seasonality (Almagro et al ., 2015; Berenstecher et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%